Deskripsi Kemampuan Kognitif Siswa pada Materi Struktur Atom - Ischak, Netty Ino; Domu, Siti Afdianti; Botutihe, Deasy Natalia; Salimi, Yuszda K.; Rumape, Opir; Aman, La Ode; Najmah, Najmah (Universitas Negeri Gorontalo, 2023)
This research aims to determine the cognitive abilities of students in atomic structure material at SMA Negeri 1 Kabila. This research is descriptive qualitative research. This research was conducted at SMA Negeri 1 Kabila with a research sample of 66 students. Data collection uses instruments in the form of a two-tier multiple choice test. Research describing the cognitive abilities of students at SMA Negeri 1 Kabila on atomic structure material. The percentage of students' cognitive aspect abilities in the high category was (36%), in the medium category was (39%), and in the low category was (31%).